PRODUCTION MACHINE INFORMATION SYSTEM BASED ON TECHNOLOGY GROUP IN RELATIONAL DATABASE ENVIRONMENT - Farhan, Ahmad; Sumantri, Yeni; Santoso, Purnomo Budi (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
The world is entering industry 4.0. The digital enlarges to machine maintenance known as troubleshooting. Troubleshooting is a series of actions needed to deal with machine damage treatment. Problems that often occur in troubleshooting are that technicians are not in the location, the information is still in the form of printed books, the risk of books being lost, books slipping, and the location of books far from the location of machine failure. This research was to solve this problem by developing an application called Production Machine Troubleshooting Information System (SITMEP) in relational database environment. This system was developed by integrating several methods such as machine damage knowledge obtained from tacit sourced from mechanical technicians, experts in their fields and explicit knowledge sourced from machine manual books. GT is to combine knowledge with machine hierarchies and it supports systems for database and SQL. The tool used was MS Access with VBA.